Pencegahan Stunting Melalui Edukasi Kesehatan Di Dusun I Desa E Wonokerto Kec. Tugumulyo Kab. Musi Rawas - Desni Herfi; Sulastri, Wiji; Reni, Febriyanti Mustika; Fauzi, Yusran (Jurnal Pakar Pengabdian Kesehatan, 2025)
Toddlers who experience long-term malnutrition, especially in the first 1000 days of life, can experience growth failure or commonly called stunting. Indonesia has a target to reduce the incidence rate to 14% by 2024. The results of the 2022 Indonesian Nutritional Status Study (SSGI) showed that the prevalence of stunting in toddlers in Indonesia was 21.6% (Ministry of Health of the Republic of Indonesia, 2022). The government has set a target to reduce stunting to 14% by 2024. Although there has been a decline, the prevalence of stunting in Indonesia is still high, at 19.8%. In dusun I, village of E Wonokerto, there are 12 out of 45 toddlers who experience stunting. The government and the entire community must play a role in efforts to achieve the 2030 stunting target. Continuous education is considered to be one way to reduce stunting rates. This activity aims to increase public knowledge including pregnant women and Posyandu cadres so that they can recognize stunting, know prevention efforts, and manage stunting. The method used in this activity is through counseling activities containing material about stunting, causes and impacts of stunting and how to prevent stunting starting from the first 1000 days of life. The activity lasts for 120 minutes. The level of knowledge of participants is measured before and after the activity through questions and answers. This activity has succeeded in increasing public knowledge. All components of society are expected to be able to actively participate in efforts to reduce the incidence of stunting.